Visible e invisible (2020)
His physical image comes to me only through photos and I tried to put together his way of being from memories and testimonies of other people; It is a good image, almost perfect and I think that those are all the qualities that someone wishes they had, because nobody says anything bad about someone who no longer exists. Possibly the construction of this image is due to the fact that many want to keep the good memory of the person and transmit it in that way. For some time now I have felt the need to build my own image of someone who is no longer with me, and it seems to me that a good starting point is the few memories I have of him.